In vivo molecular imaging of gastric cancer in human-murine xenograft models with confocal laser endomicroscopy using a tumor vascular homing peptide. Issue 2 (28th January 2015) - Liu, Lijuan; Yin, Jipeng; Liu, Changhao; Guan, Guofeng; Shi, Doufei; Wang, Xiaojuan; Xu, Bing; Tian, Zuhong; Zhao, Jing; Nie, Yongzhan; Wang, Biaoluo; Liang, Shuhui; et al.
Highlights: GEBP11 could be observed specifically bind to co-HUVECs by means of CLE in cell experiments. Specific signal could be observed in both models as well as surgical specimens of patients with gastric cancer. Ex vivo immunofluorescence of cryostatic sections microscopy findings were correlated well with CLE. Targeted molecular imaging using FITC-GEBP11 is possible with CLE both in rodent models and human tissues. Abstract: The early detection of premalignant lesions and cancers are very important for improving the survival of patients with gastric malignancies. Confocal laser endomicroscopy (CLE) is a novel imaging tool for achieving real-time microscopy during the ongoing endoscopy at subcellular resolution. In the present study, to evaluate the feasibility of real-time molecular imaging of GEBP11 by CLE in gastric cancer, CLE was performed on two types of tumor-bearing mice models, as well as surgical specimens of patients with gastric cancer, after the application of GEBP11. A whole-body fluorescent imaging device was first used to screen for the strongest specific fluorescent signal in xenograft models. Next, the tumor sites, as well as human tissues, were scanned with CLE. After this, targeted specimens were obtained for fluorescence microscopy and histology. We confirmed that GEBP11 could specifically bind to co-HUVECs by means of CLE in cell experiments. Thereafter, a specific signal was observed in both subcutaneous and orthotopic xenograft models in vivo after the injection of FITC-GEBP11 via tail vein, whereas the group injected with FITC-URP showed no fluorescent signals. In human tissues, a specific signal of GEBP11 was observed in 26/28 neoplastic specimens and in 8/28 samples of non-neoplastic specimens from the patients ( p < 0.01). The findings from ex vivo immunofluorescence microscopy of cryostat sections correlated well with that obtained by CLE. These findings indicate that the peptide, GEBP11, might be a potential candidate for the molecular imaging of gastric cancer.